Teachers’ conceptions of music teaching: A systematic literature review 2010-2020 - Karla Valdebenito; Alejandro Almonacid-Fierro (International Journal of Evaluation and Research in Education (IJERE), 2022)
This article provides an overview of research in music education between 2010 and 2020 and affords a systematic review of literature related to the experiences of teachers in teaching music in the classroom. The literature reports that music teaching depends mostly on the teacher, who must employ teaching-learning strategies according to the initial training received and the different educational contexts of professional practice. The article has the objective of analyzing the teaching practices that teachers deploy in the regular classroom of primary and secondary education. Bibliographic information was collected from the Web of Science, Scopus, and EBSCO databases. The inclusion of studies was based on having the elements of the search strategy and the selection process through inclusion criteria according to the stated objective. There were 21 selected articles. The results indicate that musical interventions by teachers in the classroom depends on some factors: i) Socioeconomic context of the educational institution; ii) Educational policies, initial teacher training; and iii) Insufficient support for this discipline. The conclusion according to the teachers’ perceptions indicate that music teaching depends on the purposes of the educational institution, the professional development of the teacher, and the teacher's preparation in the management of musical content and teaching skills.